Mechanical Hazard Simulator of PLC-Based Automation Technology According to ISO 12100 - Nur Muhammad Malikul 'Adil; Rian Dwi Aji Saputro; Firdaus Ashari (Jurnal E-Komtek, 2025)
Automation technology is expected can enhance productivity, reduce unnecessary cost, and avoid the potential upcoming accidents. However, many automation machineries don’t fulfil safety requirements and have no third party safety certification. This situation requires internal risk assessment as a gate before technology deployment in order to reduce potential hazardous events. This research applies internal risk assessment of Programmable Logic Controller (PLC)-based automation technology according to ISO 12100. Mechanical hazard simulator is built to describe the potential hazard and estimate risk level. Alternative solutions for technology retrofit is selected and built to reduce risk level. At the end of the research, risk level comparison is presented as the evidence of risk level reduction.